The capacity and effectiveness of diosmectite and charcoal in trapping the compounds causing the most frequent intoxications in acute medicine: A comparative study - Mináriková, Michaela; Fojtikova, Veronika; Vyskočilová, Eliška; Sedláček, Jan; Šikut, Milan; Borek-Dohalska, Lucie; Stiborová, Marie; Martinkova, Marketa (Environmental toxicology and pharmacology, 2017)
The aim of the study was to compare the adsorption ability of two adsorbent materials, namely diosmectite and activated charcoal towards selected model compounds that are most commonly involved in acute intoxication. Eleven model compounds were selected: acetylsalicylic acid, α-amanitin, amlodipine, digoxin, phenobarbital, ibuprofen, imipramine, carbamazepine, oxazepam, promethazine, and theophylline. Of the tested compounds, promethazine and imipramine were the most effectively adsorbed to diosmectite. Their adsorption to diosmectite (0.356±0.029mg promethazine/mg diosmectite and 0.354±0.019mg imipramine/mg diosmectite, respectively) was significantly higher than their adsorption to activated charcoal. The effect of temperature and pH on the adsorption efficiencies was also evaluated. In the case of experiments with mixture of both adsorbents, they mostly behaved in a solution independently or in a slightly antagonistic way. Using various methods such as N2 adsorption and thermogravimetric analysis, the structure and texture of diosmectite and activated charcoal were attained.
Keywords: Carbamazepine; imipramin; Diosmectite; alfa-amanitin; theofylin; Digoxin; Theophylline; antidota; ibuprofen; oxazepam; amlodipin; Amlodipine; Alpha-Amanitin; Poisoning; digoxin; Silicates; Promethazine; Acute intoxication; Oxazepam; Imipramine; Adsorption; Ibuprofen; Phenobarbital; Aspirin; otrava; adsorpce; karbamazepin; promethazin; Charcoal; dřevěné a živočišné uhlí; fenobarbital; silikáty; Antidotes